Digital-Based Media Organization Communication Strategy: An Ethnomethodology Study - Gatut Priyowidodo; Chory Angela Wijayanti; Titi Nur Vidyarini (BPSDMP Kominfo Jakarta, 2021)
The purpose of this study is to find out the strategy and communication model of techno-entrepreneurs or business actors in the field of start-up business in digital media. This research uses ethnomethodology method. Data analysis techniques are carried out through conversation analysis with the help of NVIVO 12 Software. The validity test of the data uses source and theory triangulation. The findings of this study cover two important aspects. The first communication strategy used in digital media management. Includes six things, namely management of communication, the use of communication channels, planning carried out by institutions, communication channels to drive the wheels of the organization, communication media used and who are the parties involved as communicators for both internal and external. The second finding is the factors that influence the formation of the strategy includes two aspects. First, it is the company's internal conditions. Digital-based business information must be supported by a combination of two core strengths. Those are professionals in information technology and professional management skills in the field of digital media. There are both relations with strong external parties. Business survival is determined by three important stakeholders. They are advertisers as sources of corporate income, sources as suppliers of production materials, and readers/subscribers as consumers.